Development of rational technology for sodium glyceroxide obtaining - Korchak, Mykola; Bliznjuk, Olga; Nekrasov, Serhii; Gavrish, Tatiana; Petrova, Olena; Shevchuk, Natalia; Strikha, Liudmyla; Kostyrkin, Oleg; Semenov, Evgeny; Saveliev, Dmytro (Eastern-European Journal of Enterprise Technologies, 2022)
The process of sodium glyceroxide obtaining by the reaction of glycerol and sodium hydroxide in the form of an aqueous solution was investigated. Glycerol salts (metal glyceroxides) are important components in the synthesis of many compounds. Glyceroxides are used in the chemical industry, construction, medical practice, etc. Glyceroxides of alkali metals are used in the production of modified fats and biodiesel fuel. P.a.-grade glycerol (CAS Number 56-81-5) was used with a mass fraction of the main substance of 99.5 %. The parameters of sodium hydroxide (CAS Number 1310-73-2) were studied: the mass fraction of the main substance is 98.0 %, the mass fraction of sodium carbonate is 0.5%. Rational conditions for sodium glyceroxide obtaining were determined: temperature (145 °C) and concentration of sodium hydroxide solution (65 %). Under these conditions, the mass fraction of the main substance in the product was 80 %. The melting point (72 °C) and mass fraction of moisture (0.3 %) in sodium glyceroxide were determined. The catalytic activity of the product in the process of transesterification of palm olein was tested. The increase in the melting point of palm olein was 15 °C. Under similar conditions of using potassium glyceroxide with a mass fraction of the main substance of 75.77 %, the increase in the melting point is 12.1 °C. This indicates an increase in the efficiency of the transesterification process using sodium glyceroxide obtained by the developed technology. The research results make it possible to produce sodium glyceroxide under rational conditions with a high mass fraction of the main substance at enterprises that use metal glyceroxides as a production component or commercial product. The determined rational conditions will make it possible to effectively use the company’s resources and predict the quality of the final product